Evaluasi Usability pada Aplikasi JAKI menggunakan Pengujian Usability - Muhammad Rodhi Rabbani Fadhlurrahman; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
JAKI was released by the Jakarta Smart City team in September 2019. JAKI is an application which able to access various kinds of official information and public services from the DKI Jakarta's Government. JAKI is currently 3.3 by rating on a scale of 1 to 5 on the iOS platform. Based on the observations of user reviews on the App store, it gets a lot of bad reviews from the users. So far, there's no usability evaluation of the JAKI application that has been found. Therefore, an evaluation is needed to determine the quality of the application coincide with the expectations and needs of the user in order to achieve the JAKI's goals. Usability evaluation in this study was carried out using the usability testing method. The evaluation results were obtained from usability testing data, interview data, and also observations. Usability testing is done by giving task scenarios to 5 respondents with a total of 4 tasks for each respondent. Overall, 17 of the 20 tasks were successfully completed with a success rate of 85%. From the results of interviews and observations found 41 problems. 28 problems were found from the interviews and 13 problems were found from the observations. The most common problems found is where users having difficulties finding the location of the desired features, some features and information needed by users are unavailable in the application, and from the server and integration side is not yet optimal which lead many bugs occur. There are 21 recommendations in accordance with the existing problems.